The analysis of rainwater harvesting carrying capacity on water domestic supply for dwelling areas in Indonesia - Susilo, Gatot Eko; Jafri, Muhammad (Fakultas Teknik UB, 2019)
This research aims to promote the method to design rainwater harvesting facilities in Indonesian dwelling areas. The estimation of rainwater harvesting (RWH) carrying capacity is undertaken using a simulation involving rainfall, inflow, and outflow data. The research was undertaken in Natar sub-district, Southern Lampung, Indonesia. Daily rainfall data from Branti Airport from 2013 to 2017 are used for the simulation. Research shows that houses in the study area can supply approximately 35% of their domestic water needs by applying RWH. This means that the support capacity of rainwater harvesting in the study area revolves around that value. The research also shows intensity of rainfall will greatly affect the carrying capacity of RWH. In addition to rainfall, the economic ability of a family plays an important role in planning the dimensions of a RWH facility in a house. Finally, maintenance of RWH facilities on a regular basis is important to ensure the operational effectiveness of RWH.